OZONISASI EMAS DALAM LARUTAN NaCl - Sensustania, Herinda; Tjahjanto, Rachmat Triandi; Purwonughroho, Danar (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
The aim of research about gold ozonation in NaCl solution are to determine whether gold in NaCl solution can be oxidized by ozone. In addition to know the effect of pH NaCl solution to gold ozonation. In this studied gold was ozonized for four hours at different pH of the solution. The result of this research shows that gold can be oxidized to Au3+ on the conditions used. Based on the results, it can be concluded that pH of the NaCl solution having an effect on gold ozonation. The maximum gold oxidation was occured in NaCl solution 3 M at pH 0.   Keywords: ozonation, gold, oxidation, sodium chloride, pH